Stimuli‐Responsive DNA‐Gated Nanoscale Porous Carbon Derived from ZIF‐8. (17th June 2019) - Cao, Xiyue; Xia, Jianfei; Meng, Xuan; Xu, Jiaoyan; Liu, Qingyun; Wang, Zonghua
Abstract: Stimuli‐responsive nanoscale porous carbon derived from ZIF‐8 (NCZIF) gated by DNA capping units is reported. The NCZIF is first obtained by calcination of nano‐ZIF‐8 crystals under an inert atmosphere. It is further conjugated with amine‐modified single‐stranded DNA after carboxylation (DNA/NCZIF). The guest molecules are sealed in the pore of NCZIF by the formation of a DNA duplex structure on the surface of NCZIF. As proof of principle, two systems that can be, respectively, used for controlled drug delivery and biosensing are introduced. In the first system, the drug model (rhodamine 6G, Rh6G) is locked in the NCZIF by the DNA capping units composed of rich‐G sequences and its complementary DNA strand. The in vitro cellular experiments reveal that DNA/NCZIF has good biocompatibility and can controllably release Rh6G upon the K + ‐stimuli in cells. In the second system, the signal probe (methylene blue, MB) is locked in the NCZIF and then released after the unlocking of the pores triggered by the dissociation of the aptamer‐hybrid capping units. The MB‐loaded DNA/NCZIF can linearly respond to target molecules in the range from 1 × 10 −9 to 10 × 10 −6 m and has good specificity. Abstract : A novel design of stimuli‐responsive DNA‐gated nanoscale porous carbon derived from ZIF‐8 (DNA/NCZIF) is reported. The as‐synthesized DNA/NCZIF, possessing good loading and releasing profiles and a facile synthesis method, can controllably release rhodamine 6G (or methylene blue upon the stimuli of K + ions (or lysozymes), which can be applied for controlled drug delivery and homogeneous biosensing assays, respectively.